2017
DOI: 10.3390/rs9111174
|View full text |Cite
|
Sign up to set email alerts
|

A Hyperspectral Imaging Approach to White Matter Hyperintensities Detection in Brain Magnetic Resonance Images

Abstract: White matter hyperintensities (WMHs) are closely related to various geriatric disorders including cerebrovascular diseases, cardiovascular diseases, dementia, and psychiatric disorders of elderly people, and can be generally detected on T2 weighted (T2W) or fluid attenuation inversion recovery (FLAIR) brain magnetic resonance (MR) images. This paper develops a new approach to detect WMH in MR brain images from a hyperspectral imaging perspective. To take advantage of hyperspectral imaging, a nonlinear band exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Previous studies [25, 30, 31] have indicated that combining pixel spectral and spatial information increases the accuracy of hyperspectral image classification. Therefore, we used the ILCMV method to classify cell subpixels in the hyperspectral image and measured their average spectral profile for subsequent spectral difference analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies [25, 30, 31] have indicated that combining pixel spectral and spatial information increases the accuracy of hyperspectral image classification. Therefore, we used the ILCMV method to classify cell subpixels in the hyperspectral image and measured their average spectral profile for subsequent spectral difference analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, fMRI is used to study brain development in infants [2,[24][25][26][27][28]. rs-fMRI, gray matter (GM), and white matter (WM) MRI [29] has been used to diagnose brain abnormalities that cause ASD in several studies. Alongside the rapid advancement of both medical and computing technologies, there has been a corresponding rise in the commercial and educational interest in the field of healthcare.…”
Section: > Replace This Line With Your Manuscript Id Number (Double-c...mentioning
confidence: 99%
“…To obtain MRS signal waveform with higher fidelity after ISSR, we define the basic frequency f prop , and its unit is Hz. f prop can be understood as the sampling frequency of the reconstructed signal, which satisfies the sampling theorem and is less than f s H , as formula (4).…”
Section: Basic Frequency Of Sparse Reconstructionmentioning
confidence: 99%
“…MRS is a relatively efficient and non-invasive geophysical approach for groundwater surveying that utilizes the principle of magnetic resonance phenomenon in hydrogen atoms comprised of water in the geomagnetic field [1][2][3]. The development of nuclear magnetic resonance imaging in the biomedical field has promoted the MRS application in water resources exploration [4,5]. So far, the MRS method and instrument have been further researched and developed in many countries such as France, the United States, Germany, China and other countries [6][7][8].…”
Section: Introductionmentioning
confidence: 99%